(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The amendments to the Constitution do not concern the secular character of the State and the principle of separation between State and Church. However, there is a conflict between the Constitution and the ordinary laws in force, since the latter violate the principle of state secularism and that of separation between State and Church. The mention of God in the Constitution does not infringe the principle of state secularism since it is not referred to any specific Church or religious confession and does not intend to influence citizens in the religious field.